Soda Taxes and the Prices of Sodas and Other Drinks: Evidence from Mexico - Jeff Grogger (Institute for the Study of Labor (IZA), 2016)
To combat a growing obesity problem, Mexico imposed a nationwide tax on drinks with added sugar, popularly referred to as a "soda tax," effective January 2014. Since the tax took effect nationwide, there is no conventional control group that can be used as a baseline to estimate how the tax affected prices. Instead, I make use of control commodities, that is, untaxed goods that are not substitutes for the taxed drinks. I analyze data from Mexico's Consumer Price Index program, using the synthetic control method and a time-series intervention analysis. I employ a placebo inference approach, akin to permutation inference, in both cases. The estimates show that soda prices rose by more than the amount of the tax. There is less evidence that the prices of potential substitutes rose, possibly indicating that consumers did not switch to those products after the tax took effect. Some simple calculations suggest that the soda price increase could lead to a two- to four-pound reduction in mean weight. This in turn amounts to roughly 1.6 to 2.7 percent of mean body mass, which compares to weight reductions that analysts have argued would have meaningful health consequences in the U.S.
Keywords: H22; I10; 330; soda taxes; overshifting; obesity